Supply Chain Strategy in Banking Sector of Russia: New Challenges and Strategic Fundamentals of Development - Strelnikov, Vladimir V. (International Journal of Supply Chain Management, 2020)
Abstract- The present study aims to examine the idea of supply chain management in the financial institutions like banks in the region of Russia. Currently, the banking sector of Russia is showing a steady improvement in key indicators - the cost of borrowing is declining, the lending to the national economy is expanding, household deposits are growing, and profits are increasing. However, the challenges of banking intensify every year. There are different views on the strategic fundamentals of banking development among the specialists and leaders of the banking sector. Particular emphasis is placed on new financial platforms and related ecosystems, focused on e-commerce and logistics priorities. This will require the development of new forms of organization, supply chain management, supervisory and regulatory control. The preservation of banking business potential requires the implementation of a long-term competitive strategy, which goes far beyond the financial sector.